A study on pedestrian crowd simulations through distributed personal mobility device (PMD) docking hubs - Ramakrishna Santhira Segaran (Nanyang Technological University, 2020)
The rise in popularity of Personal Mobility Devices (PMDs) in the last decade has taken Singapore by storm. The numerous advantages that come with PMDs secured its place in the food delivery industry. However, problems began to arise from rider behavior and lack of government regulations that resulted in many accidents involving PMD riders and pedestrians. Public outcry began to pile up and reached its fever pitch when an accident caused a loss of life. The government ultimately decided to ban the use of PMDs on public footpaths with the exception of Cycling Paths and Park Connectors. Not wanting to overlook the potential of PMDs, this research attempts to explore the implementation of PMDs as a shared service to possibly improve pedestrian network performance. This was done via a simulation software, VISSIM with a virtual rendition of Nanyang Technological University (NTU) as a campus environment. The simulation was built, and experiments were carried out with varying PMD Hub capacities, PMD Hub placement locations and area archetypes. Pedestrian network performance was measured using average pedestrian flow and average pedestrian travel time. The results show that increasing the PMD Hub capacities would increase average pedestrian flow and reduce average pedestrian travel time. On the other hand, there appears to be no conclusive results in identifying an optimal PMD Hub physical placement.